Association Between Dental Expenditure and Socioeconomic Status in Iran - Mohammad-Pooyan Jadidfard; A. Hamid Zafarmand; Sediqe Shafiei (Elsevier, 2024)
Background: Health care spending by households can be a great indicator of a society's commitment to good health stewardship and the efficiency of institutions responsible for managing health costs. Equitable and appropriate distribution of dental services is a challenging issue for realising universal health coverage. This study aimed to evaluate Iranian households' per capita dental expenditure (DE) according to their socioeconomic status (SES). Methods: In this cross-sectional study, the income and expenditure of 18,701 urban and 19,261 rural households in Iran were scrutinised according to the data provided by the Statistics Center of Iran (2017-2018). After model creation, the SES index was determined using principal component analysis and weighting based on the analytical hierarchy process. The dependent variable was the share of per capita household's expenditure spent on dental health. The zero-inflated gamma regression model was applied to confirm the presumed association between per capita DE and SES. Analyses were performed using PROC NLMIXED in SAS software (version 4.9). Results: The results revealed that approximately 9% of urban and 4% of rural households paid for dental treatments in the past month. The DE to total health expenditure (HE) ratios were 8.5% and 14.8% for rural and urban households, respectively. Also, with each level increase in SES, the average per capita DE increased by 23% and 16% in rural and urban households, respectively. Conclusions: The study confirms association between per capita DE and SES in Iran. This implies targeted strategies to facilitate the utilisation of dental care especially for lower SES groups according to their needs.